The Worship sourcebook. - Calvin Institute of Christian Worship; Faith Alive Christian Resources (Grand Rapids, Mich. : Calvin Institute of Christian Worship : Faith Alive : Baker Books, 2013)
The Worship Sourcebook is a unique resource now available for the traditional or liturgical church's worship service needs. Filled with beautiful prepared prayers, stirring liturgies, and useful service plans, it provides an alternative to the Book of Common Worship (PCUSA) that is aimed more broadly in terms of global resources for Reformed and evangelical churches. The companion CD contains the entire 800-page text for easy cutting and pasting into bulletins, overheads, and orders of worship. The Worship Sourcebookis a perfect tool for exploring traditional worship in a classroom setting.
The practice of Christian worship -- The worship sourcebook : a contemporary experiment based on classical models -- Using the worship sourcebook -- Elements of the worship service -- Opening of worship -- Confession and assurance -- Proclaiming the word -- Prayers of the people -- Offering -- Baptism -- Profession of faith and remembrance of baptism -- The Lord's supper -- Closing of worship -- Central themes of the Christian faith -- Creation -- Providence -- Thanksgiving -- Advent -- Christmas -- Epiphany -- Baptism of our Lord -- Transfiguration -- Ash Wednesday -- Lent -- Passion/Palm Sunday -- Maundy Thursday -- Good Friday -- Easter -- Ascension of our Lord -- Christ the King -- Pentecost -- Trinity Sunday -- Unity of the church -- Communion of the saints -- Appendix : Worshiping the Triune God.
Includes bibliographical references and indexes.
System requirements for accompanying CD-ROM: Adobe Acrobat Reader.
Keywords: Worship programs; Public worship -- Handbooks, manuals, etc; Liturgies; Liturgies; Public worship; Worship programs; Handbooks, manuals, etc